Selective guest exchange in encapsulation complexes using light of different wavelenghts - Dube, Henry; Rebek, Julius (Angewandte Chemie International Edition, 2012)
A matter of light: Selective control over the assembly of two distinct encapsulation complexes in solution is achieved by using light of two wavelengths and heat. Guest exchange can be triggered in a sequential or parallel fashion, depending on the wavelength applied, and three combinations of encapsulation complexes (see scheme) are accessible. Photoisomerization of azobenzene (red capsule) and hemithioindigo guests (yellow capsule) are used as triggers. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-04-02
Keywords: azobenzenes; encapsulation; host-guest systems; molecular devices; photoisomerization